Programas de reabilitação auditiva para idosos: uma proposta alternativa de avaliação de eficácia - Lombardi, Christiane Mara (2009)
Theme: The majority of the elderly people with presbycusis can benefit from group hearing rehabilitation. The literature on this subject evaluated those programs as effective. Therefore, the literature does not point the origin of this effectiveness. Based on the information collected from these literature, a private hospital located in São Paulo created the Hearing Aid User Support Group GAUAA, which consists of four monthly meetings. Purpose: To find out the effectivness of a group hearing rehabilitation program for the elderly through shifting from quantitative data to qualitative data. Method: Thirty subjects, hearing aid users with monoaural adaptation, showing moderate to severe hearing loss with ages between seventy and ninety-two years old have participated in this research. This study provided two situations: on situation I, the International Outcome Inventory for Hearing Aids questionnaire (IOI-HÁ) was applied before and after the program. The objetive was to evaluate the user degree of satisfaction. The collected data were submeted to the Wilcoxon test method analysis and analysed through the Spearman correlation method. The situation II was divided in two phases: on phase I, the subjects statements were collected and analysed after the program. At phase II, the subjects statements were analysed during the GAUAA meetings. These data were analysed by the french line of the speech analysis proposed by Orlandi(1996). Results: The data found at situation I were statistically significant, but they could not indicate what would be the reason for the positive effectiveness responses from the clinical perpective. Thus, the situation II through the qualitative analysis, made possible to observe the subjects singularities, which suggested that the effectiveness of a hearing rehabilitation program is due to the identification among the participants and by transference, sustained by the coordinator´s position. The GAUAA effectiveness derives from the ludical speech dominance, which its effects promote the effectiveness of the hearing aid use